Private equity: impacto no retorno das ações de empresas do setor elétrico no Brasil - Dâmaso, Ligianne Carvalho da Silva (2017)
Recently, Brazil has taken an outstanding position as one of the most attractive emerging markets for Private Equity investment in sectors related to infrastructure, specially the Power Sector. One of the major short-term structural challenges for this segment is the need to attract new capital. From this point of view, the Private Equity market may intensify its activity as an additional source of financial resources for this strategic sector. The main purpose of this research was to verify if the return of Power Sector companies’ stocks listed on BM&FBOVESPA is statistically significant and different due to the Private Equity investments presence. Two portfolio investment with and without Private Equity were examined. The performance was measured by the Sharpe Index in order to capture the risk-adjusted return. The robust method of Ledoit & Wolf (2008) was applied to evaluate the difference between Sharpe indices and to verify the hypothesis of this study. The results indicated that the Private Equity portfolio showed, on average, a higher statistical significant Sharpe Index even before the Provisional Act no. 579 of September 11, 2012, which corroborated to lower volatility and greater cumulative return of stocks in the period between 2010 and 2016. In addition, there are evidences to support a higher return on the Private Equity portfolio, since the portfolio of companies without Private Equity showed decreasing average for Return on Assets and Return on Equity indicators and unsatisfactory performance for the indices that make up the DuPont Model